Pediatric hepatocellular carcinoma associated with Niemann–Pick disease type C: Case report and literature review. Issue 1 (9th November 2022) - Hwang, Soojin; Choi, Yunha; Lee, Beom Hee; Choi, Jin‐Ho; Kim, Ja Hye; Yoo, Han‐Wook
Abstract: Niemann–Pick disease type C (NPC) is a rare, autosomal recessive, lysosomal storage disease, resulting from mutations in the cholesterol trafficking proteins NPC1 or NPC2, which is characterized by progressive neurodegeneration and hepatic dysfunction. The hepatic involvement in NPC is usually neonatal cholestasis and hepatosplenomegaly. Only a few cases of severe hepatic complications were reported including acute liver failure, cirrhosis, and hepatocellular carcinoma (HCC). We described the case of a 6‐year‐old male with NPC with HCC. He had a history of neonatal cholestasis and motor delay. At the age of 6 months, he was diagnosed with NPC, which was confirmed by the detection of a compound heterozygous NPC1 mutation (p.C113Y/p.A927V). He presented recurrent hypoglycemia and abdominal distension. An ultrasound, computed tomography scan, and biopsy revealed that he had a stage IV HCC with pulmonary metastasis. With the literature review and this case, HCC can be a rare fatal comorbid condition in patients with NPC, particularly infantile‐onset, male patients with a relatively long disease history, necessitating appropriate HCC surveillance.